(untitled) (Journal of Ideas in Health, 2021)
Background: Among the most popular methods employed to classify the depth of the olfactory fossa is Keros classification. This study aims to assess Keros classification of the ethmoid roof, any possible association between Keros types and gender, and the incidence of asymmetry between right and left sides among Iraqi patients. Methods: A retrospective cross-sectional study was conducted at Al-Shaheed Gazi Al-Hariri Teaching Hospital, Medical City, Baghdad, Iraq. The archived reports and the CT scans images (nose and paranasal sinuses) of 126 patients who have undergone functional endoscopic sinus surgery between January 2019 and January 2020 were reviewed. Univariate and bivariate statistical analysis was performed using SPSS version 24. The statistically significant was considered at less than 0.05. Results: More than half of patients were females (54.0%) with a mean age of 31.52 ± 11.38 (SD) years (range: 10-57 years). Among the total patients, the mean depth of olfactory fossa (OF) was 3.58 ± 0.02 mm. Results showed that Keros type I was the most common type (71.0%), followed by type II (27.4%) and type III (1.6%) respectively. The difference in the olfactory fossa depth between the right and left sides was ≥ 1 mm in 16 (12.7%) patients and < 1 mm in 110 (87.3%) patients. Moreover, there was no significant relation between symmetry/asymmetry and gender ( p-value > 0.05). Conclusion: Keros type I was the most common type, which carries the lowest risk of inadvertent intracranial injury during endoscopic sinus surgery; besides the relatively low percentage of asymmetry in the depth of the two olfactory fossae among patients, surgeons should always be cautious during surgery to avoid iatrogenic injury concerning the thin lateral lamella of the cribriform plate.